Kryzys Kościoła jako kryzys wartości w niemieckim dyskursie teologiczno-socjologicznym - Zduniak, Agnieszka (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2019)
The article is devoted to changes occurring in the axionormative sphere, which result is a change in the situation of the Church in society. It is often referred to as a crisis. The author presents the most important threads of the discussion, which has been going on for several decades in the environment of German theologians and sociologists. They identify the reasons for the weakening of the role of church institutions and point out the possibilities of remedying these problems. The situation of the Catholic Church in Germany is different than in Poland, but similar trends in social and cultural development, including changes taking place in the sphere of values, might lead to the Church of Poland facing similar issues in the future. Therefore, structural and pastoral changes may also be needed in the Polish Church, to increase the effectiveness of preaching the Gospel to modern man.